Production of Copper Radionuclides in Compact Medical Cyclotrons using Solid Targets - Avila-Rodriguez, Miguel A.; Valdovinos, Hector F. (Current Radiopharmaceuticals, 2021)
Over the last several years there has been a growing interest in the use of radiopharmaceuticals labeled with metallic radionuclides, especially isotopes of copper (Cu). Cu has a unique set of radionuclides with a potential application not only for diagnostic imaging but also for applications in targeted radionuclide therapy. To review the methods and routes used for the production of Cu radionuclides in compact medical cyclotrons (Ep<20 MeV) using solid targets. The cyclotron production of Cu radionuclides using solid targets has proven to be very efficient. The large number of compact medical cyclotrons distributed worldwide, and the high target yields in the production of Cu radionuclides achieved at these energies, form a potential network of distribution to satisfy the growing demand for these radionuclides, especially 64Cu.
Keywords: Cu-64